2010
DOI: 10.1097/prs.0b013e3181d51227
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Predictors of Failure after Flap Coverage of Pressure Ulcers

Abstract: Confirmation of adequate nutritional status and strict preoperative management of blood glucose may improve operative success rates. The authors propose that operative management should be approached with trepidation, if at all, in young patients with recurrent ischial ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
132
6
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(153 citation statements)
references
References 28 publications
12
132
6
3
Order By: Relevance
“…Absolutely bed rest after operation should be emphasized repeatedly to these patients. Our study confirmed the conclusion of several earlier studies, namely that there is no significant difference among different surgical approaches in terms of complication or recurrence rates (3,6,7). However, little is known about the correlation between our described possible risk factors and the complication/recurrence rates in specific reconstruction methods.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 91%
See 4 more Smart Citations
“…Absolutely bed rest after operation should be emphasized repeatedly to these patients. Our study confirmed the conclusion of several earlier studies, namely that there is no significant difference among different surgical approaches in terms of complication or recurrence rates (3,6,7). However, little is known about the correlation between our described possible risk factors and the complication/recurrence rates in specific reconstruction methods.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 91%
“…We considered gender, surgical method, age > 45 years at the time of surgery, wound location, defect size exceeding 50 cm 2 , pre-surgical albumin level less than or equal to 3.0g/dl, previous flap failure, paraplegia status, the existence of other concurrent ulcers, and medical history of diabetes as potential confounders in the analysis, according to previous studies (3,6,9). We performed the multivariable logistic regression model using forward elimination to control for each patient's specific effect on wound complication and recurrence rates while adjusting for confounding variables.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations